Clinical Outcomes of Implantable Collamer Lenses for the Treatment of Myopia in Eyes with Anterior Chamber Depth (<3.0 mm) at a Single Center in the United States [Letter] - Chaurasiya SK; Bandyopadhyay A; Chaithu SA (Clinical Ophthalmology)
Suraj Kumar Chaurasiya,1 Ankita Bandyopadhyay,2 Sarakham Aimol Chaithu3 1Department of Optometry and Vision Science, CL Gupta Eye Institute, Moradabad, UP, 244001, India; 2Department of Optometry, School of Paramedics and Allied Health Science, Centurion University, Bhubaneswar, 750017, India; 3Department of Optometry and Vision Science, RIPANS (Regional Institute of Paramedical and Nursing Sciences), Aizawl, IndiaCorrespondence: Suraj Kumar Chaurasiya, CL Gupta Eye Institute, Ram Ganga Vihar Phase II (Extn.), Moradabad, Uttar Pradesh, 244001, India, Tel +91 8809893186, Email csurajk414@gmail.com